2020
DOI: 10.3389/fevo.2020.569730
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Environmental and Social Factors on Perceived Bio-Cultural Services and Disservices

Abstract: Although the value of urban ecological infrastructure (UEI) is widely recognized, insufficient research has investigated how people perceive the wide variety of UEI. To address this gap, we investigated residents' perceptions of the coupled value of aesthetic and biological qualities as related to diverse UEI and other environmental and social factors (including personal beliefs and demographics), collectively referred to as bio-cultural services and disservices. We evaluated whether people positively view the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 103 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…ES and EDS are generally provided by the same urban greenspace but often EDS are over-reported. That seems at least partially influenced by societal mainstream appreciation while the basic or deep knowledge on bio-cultural services and disservices shown by the respondents apparently does not influence perception and reporting on the positive value of ES [47].…”
Section: Species Preferencesmentioning
confidence: 84%
“…ES and EDS are generally provided by the same urban greenspace but often EDS are over-reported. That seems at least partially influenced by societal mainstream appreciation while the basic or deep knowledge on bio-cultural services and disservices shown by the respondents apparently does not influence perception and reporting on the positive value of ES [47].…”
Section: Species Preferencesmentioning
confidence: 84%
“…Also, caution must be granted to the implications of our results, since a common awareness and perception of the impacts of climate change on ES does not necessarily translate into effective governmental engagement in the prioritization of this matter in action-oriented decision-making (Hummel et al, 2017;Luís et al, 2018). In addition, diversified engagement from citizens and other relevant private and public entities should also be accounted (Runting et al, 2017;Brown et al, 2020). Subsequent research should explore to what extent the awareness of climate change impacts in ES is effectively incorporated into regional planning and management, given their influence in decision-making processes shaping large portions of the landscape.…”
Section: Research Limitations and Prospectsmentioning
confidence: 97%
“…Specifically, the sprawling outward growth of cities has surrounded and isolated remnants of desert within a matrix of human development and agriculture, putting certain residents in closer proximity to the desert parks and preserves (Andrade et al, 2019). For instance, previous research in the region has shown that how close residents live to these desert parks tend to be wealthier, have more positive attitudes toward the desert, and experience higher wildlife diversity and greater ecosystem services (Andrade et al, 2019;Warren et al, 2019;Brown, 2020).…”
Section: Study Systemmentioning
confidence: 99%